FAKTOR PENYEBAB WANPRESTASI PELAKSANAAN PERJANJIAN SEWA BELI SEPEDA MOTOR DI PT. ADIRA FINANCE MATARAM - APRIANI, TITIN; SARI, NI LUH ARININGSIH; ARTANA, I NYOMAN JAYA (GANEC SWARA, 2018)
The purpose of this study to determine the factors that cause wanprestasi in the implementation of rental agreement to buy a motorcycle. This research is empirical juridical research, with data collection technique done by literature study and interview. Data were analyzed using qualitative descriptive approach method.The result of the research shows that the cause of motorcycle lease wanprestasi due to the implementation of target system by the company to employees and employees of the company to assist the lease purchase process, although basically the prospective consumer is known will not be able to give installment on every month, so if there is wanprestasi, then it can be done with the way deliberation and consensus and if the case can not be resolved by consensus mufakat it will be resolved through court or litigation path.